Phytochemicals from Entada spiralis Ridl. and Tetracera macrophylla Vall. and their bioactivities - Roheem, Fatimah Opeyemi (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Digestive enzymes and free radical inhibitors are used to control hyperglycemia and prevent diabetes complications. With the aim of continuous search for plant derived inhibitors, two medicinal plants that are well known in herbal medicine due to its various traditional and medicinal applications were studied. Namely; Entada spiralis Ridl. stem bark (Leguminosae) and Tetracera macrophylla vall. (Dilleniaceae). E. spiralis crude extracts were successively extracted from the stem bark using petroleum ether, chloroform and methanol as extracting solvents while T. macrophylla leaves were extracted using ethanol (95%). All the extracts were analyzed for their total phenolics and flavonoid contents. 2, 2diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azinobis-3-ethylbenzothiazine-6-sulfonic acid (ABTS) and β-carotene bleaching assays were used to examine the antioxidant capacity while digestive enzyme inhibitory activity was assessed using α-amylase and α-glucosidase inhibitory methods respectively all by in vitro models. Methanol extract of E. spiralis stem bark contained the highest amount of total phenolics and exhibited highest activity against β-carotene bleaching inhibition, DPPH, ABTS radicals and digestive enzymes. Similarly, ethanol extract of T. macrophylla leave was found to be rich in both phenolic and flavonoid contents and exhibited good antioxidant and digestive enzyme inhibitory activities. Methanol extract of E. spiralis was further fractionated using column chromatography since it displayed the most potent activity against free radicals and digestive enzymes to obtain F1, F2, F3 and F4. Among all the fractions, F1 and F2 were found to display highest contents of phenolics and flavonoids and therefore demonstrated highest antioxidant and digestive enzyme inhibitory activities. Also, fractionation of ethanol extract of T. macrophylla leaves through liquid-liquid partitioning yielded fractions Fa, Fb, Fc, and Fd. Among all the fractions, Fb showed the highest phenolic and flavonoid contents and was also found to exhibit highest antioxidant and enzyme inhibitory activities. F1 and F2 which are the most active fractions of methanol extract of E. spiralis stem bark were then subjected to different chromatographic techniques to afford eight compounds. All the compounds isolated were characterized and identified through different spectroscopic techniques such as UV, FTIR, NMR and mass spectrometry. The compounds were identified as ergosta-5, 7-dien-3-ol 1a, hexyl 3-(4-hydroxy-3-methoxyphenyl) acrylate 2a, kaempferol 3a, pachypodol 4a, gallic acid 5a, lupeol 6a, +(-) catechin 7a and –(-) epicatechin 8a. Interestingly, this is the first scientific report for the isolation of ergosta-5, 7-dien-3-ol and hexyl 3-(4-hydroxy-3-methoxyphenyl) acrylate from plant. For T. macrophylla leave Fb which was the most active fraction was also purified on column chromatography to obtain five compounds Namely; 5, 7 di-hydroxy-8-methoxy flavone 1b, betulinic acid 2b, kaempferol 3b, quercetin 4b, 5,7,8-trihydroxy flavone 6b. Compounds 5a and 4b exhibited highest activity against both enzymes and free radicals. Twelve out of all the compounds isolated from both plants displayed good antioxidant and/or digestive enzyme inhibitory activity.